2007
DOI: 10.1007/s10529-007-9536-x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of a novel endo-β-1,4-glucanase from the thermoacidophilic Aspergillus terreus

Abstract: An endo-beta-1,4-glucanase from a thermoacidophilic fungus, Aspergillus terreus M11, was purified 18-fold with 14% yield and a specific activity of 67 U mg(-1) protein. The optimal pH was 2 and the cellulase was stable from pH 2 to 5. The cellulase had a temperature optimum of 60 degrees C measured over 30 min and retained more than 60% of its activity after heating at 70 degrees C for 1 h. The molecular mass of the cellulase was about 25 kDa. Its activity was inhibited by 77% by Hg(2+) (2 mM) and by 59% by Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 14 publications
(3 reference statements)
6
23
1
2
Order By: Relevance
“…EDTA had much less of an effect on the activity. The CAEG was found to be resistant to SDS and Triton X-100, having a relative activity above 80%, which was found to be high when compared with other reports (Gao et al, 2008;Elshafei et al, 2009). 3.4.6.…”
Section: +mentioning
confidence: 53%
See 2 more Smart Citations
“…EDTA had much less of an effect on the activity. The CAEG was found to be resistant to SDS and Triton X-100, having a relative activity above 80%, which was found to be high when compared with other reports (Gao et al, 2008;Elshafei et al, 2009). 3.4.6.…”
Section: +mentioning
confidence: 53%
“…The optimum pH for the stability of EG from A. terreus strain AKM-F3 was found to be pH 7.0 (100% relative EG activity = 26.17 U/mg) and almost 90% of relative activity was shown at pH 5.0-8.0 ( Figure 13). The EG from A. terreus M11 was stable at pH 2.0-5.0 (Gao et al, 2008), while the EG from A. terreus strain AN 1 was stable at pH 3.0-5.0 (Nazir et al, 2009). Acids or bases alter a protein's 3D structure because the H + and OH -compete with the hydrogen and ionic bonds in an enzyme, resulting in denaturation (Tortora et al, 2004).…”
Section: The Effect Of Ph On the Activity And Stability Of Caegmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the cellulase produced by A. niger IFO31125 showed an optimum temperature of around 70°C at pH 6 with stability for 2 h [71]. The pH and the temperature optima of the cellulase produced by A. terreus M11 was found as 2 and 60°C, respectively; and 60% of the initial activity was maintained for 1 h at 70°C [72]. Two endoglucanases, RCE1 and RCE2 produced by Rhizopus oryzae showed 55°C as the optimum temperature for both the enzymes with different pH optima, i.e., 5 and 6, respectively [73].…”
Section: Statistical Optimizationmentioning
confidence: 97%
“…Riou et al [74] investigated the effect of different metal ions and detergents on cellulase produced by A. oryzae, and found that Ag + , Hg 2+ Fe 3+ , SDS, diethylpyrocarbonate, castanospermine, dithiothreitol were slightly or completely inhibited the cellulase activity; whereas Mn 2+ enhanced the activity. Similarly, the activity of cellulase produced by A. terreus M11 was increased in the presence of Mn 2+ ; but the presence of Hg 2+ , Cu 2+ , Pb 2+ and detergents slightly decreased or completely abolished the activity of cellulase [72]. Yang et al [80] demonstrated that the cellulase produced by Paecilomyces thermophila was strongly inhibited by Hg 2+ ; while the activity was highly enhanced in the presence Zn 2+ .…”
Section: Influence Of Metal Ions Detergents and Surfactantsmentioning
confidence: 99%